Program Pendampingan dan Pelatihan: Implementasi Ragam Komunikasi pada Sivitas Akademika SMA Kristoforus II Jakarta - Surianto, Surianto; Kho, Gerson Ralph Manuel; Gunarti, Destri Sari; Fensi, Fabianus; Limbong, Yosafhat Christian (Riwayat: Educational Journal of History and Humanities, 2025)
Miscommunication arises when communication between individuals is not conducted with optimal effectiveness and efficiency. This phenomenon is notably prevalent within academic environments, such as schools, which constitute a significant portion of an individual's formative yearstypically spanning 12 years. To address this issue, a structured program encompassing mentorship and training rooted in communication studies, both theoretical and practical, was implemented with the aim of mitigating instances of miscommunication. This initiative engaged a total of 124 participants, comprising 118 students and 6 teachers from Kristoforus II Senior High School in Jakarta. The training emphasized the development of public communication skills, alongside their application within the fields of psychological communication and broadcast communication. Participants provided overwhelmingly positive feedback on the training's execution, underscoring the efficacy of practical training methods. The findings reaffirm the recommendation of practical approaches as an optimal methodology for enhancing public communication competencies in educational industries.